Re-evaluating the role of the orbitofrontal cortex in reward and reinforcement. - Noonan, M; Kolling, N; Walton, M; Rushworth, M (2012)
The orbitofrontal cortex and adjacent ventromedial prefrontal cortex carry reward representations and mediate flexible behaviour when circumstances change. Here we review how recent experiments in humans and macaques have confirmed the existence of a major difference between the functions of the ventromedial prefrontal cortex and adjacent medial orbitofrontal cortex (mOFC) on the one hand and the lateral orbitofrontal cortex (lOFC) on the other. These differences, however, may not be best accounted for in terms of specializations for reward and error/punishment processing as is commonly assumed. Instead we argue that both lesion and functional magnetic resonance imaging studies reveal that the lOFC is concerned with the assignment of credit for both reward and error outcomes to the choice of specific stimuli and with the linking of specific stimulus representations to representations of specific types of reward outcome. By contrast, we argue that the ventromedial prefrontal cortex/mOFC is concerned with evaluation, value-guided decision-making and maintenance of a choice over successive decisions. Despite the popular view that they cause perseveration of behaviour and inability to inhibit repetition of a previously made choice, we found that lesions in neither orbitofrontal subdivision caused perseveration. On the contrary, lesions in the lOFC made animals switch more rapidly between choices when they were finding it difficult to assign reward values to choices. Lesions in the mOFC caused animals to lose their normal predisposition to repeat previously successful choices, suggesting that the mOFC does not just mediate value comparison in choice but also facilitates maintenance of the same choice if it has been successful.